The Normalization of Verbal Abuse in Dating Relationships Among Students of the State Islamic University of North Sumatra: A Sociology of Religion Perspective - Fatria Handewi; Neila Susanti (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines how verbal abuse becomes normalized in student dating relationships at the State Islamic University of North Sumatra and how students interpret such experiences within an Islamic academic environment. The study employed a qualitative approach with a phenomenological design to explore students’ lived experiences of verbal abuse in romantic relationships. Data were collected from nine active students aged 19–24 who had experienced verbal abuse in current or previous dating relationships. Participants were selected through purposive sampling based on three criteria: active student status, experience in dating relationships, and willingness to share personal experiences related to verbal abuse. Data were obtained through in-depth interviews, observation, and documentation, and were analyzed using thematic analysis. The findings show that verbal abuse is normalized through the repeated interpretation of jealousy, excessive control, insulting language, emotional threats, possessive behavior, demands for location sharing, and social media surveillance as expressions of affection, care, or protection. The study also reveals that unequal power relations and certain gendered cultural assumptions shape how students justify controlling behavior in dating relationships. In some cases, particular social interpretations of religious values are used to legitimize obedience, restriction, and protection, although these interpretations contradict the ethical principles of compassion, mutual respect, and emotional self-control promoted in Islamic teachings. The study concludes that verbal abuse in student dating relationships is not merely an interpersonal conflict but a social and religiously interpreted phenomenon that requires healthy relationship education, gender-sensitive religious literacy, and campus-based counseling support.